Pengembangan Asesmen Kinerja Keterampilan Inkuiri Real-World Application Pada Permasalahan Biologi SMA - Rifda Tanfiziyah; Ana Ratna Wulan; Eni Nuraeni (Universitas Pendidikan Mandalika, 2022)
This study aims to develop a test assessment as a practical performance appraisal. Real-World application inquiry skills refer to Wenning's framework for learning Biology. The study used the research and development method. The research subjects were students of class XII SMAN 2 Serang City Banten Province in the academic year 2022/2023. The research instruments were forms of tests in the form of practical tasks and rubrics. The performance assessment tool was evaluated for validity and scored 0.53. Analysis of the validity of the performance assessment using Aiken's V. Based on the criteria, the performance assessment tool was declared valid. Then, for the reliability of non-test assessment tools, the average measure's value was 0.715. It means that the performance assessment assessed by the three validators has a moderate ICC (Intraclass Correlation Coefficient) value or moderate reliability. Based on the research results, the resulting assessment tool is ready to be used directly or as an assessment prototype for further development.